Pelatihan Admin untuk Optimalisasi Website BUMDes Gemblegan Makmur, Kecamatan Kalikotes, Klaten - Renna Yanwastika Ariyana; Prita Haryani; Muhammad Nurcahyo Sasongko (Universitas Pahlawan Tuanku Tambusai, 2022)
On the website page there is information in the form of text, image, audio, video data or a combination of all that information, where the website can be accessed through a link that is interrelated with one another. There are various benefits that can be obtained from the presence of a website, including as a promotional media and access to information. Utilizing online media by building a website for BUMDes gemblegan will certainly be very useful in the process of promoting activities and products produced by the village. However, with the construction of a website, of course you need an admin who will manage the information contained in the page. This is to provide access and quality to the quality of information and products that will be displayed on the website page. Providing training to equip administrators who will become website admins is certainly very necessary, in order to manage all content on the website, both posting articles, comments, tags, categories, and media that will be inserted in the website page.